Radiation hardness of silicon Photomultipliers under 60Co γ-ray irradiation - Pagano, R. (2014)
Radiation damage in silicon photomultipliers (SiPM) caused by exposure to 60Co γ-rays is experimentally evaluated and discussed. SiPM devices were irradiated to doses up to 9.4 kGy. Dark current, dark count rate, gain, single photon counting capability, and cross-talk probability among SiPM pixels are evaluated as a function of irradiation dose.